Legal Perspective of Law No. 28 of 2014: About The Moral Aspects on Digital Works - Evelyn Angelita Pinondang Manurung (Catuspata, 2021)
The current utilization of digital content platforms has a serious impact on Intellectual Property Rights. Platforms that display digital copyright works are indeed much in demand by netizens today because it is practical and efficient but not only the perceived benefits of digital content platforms but there is a moral responsibility that must be known by all parties both content lovers and content creators. In today's digital era, copyrighted works in the form of digital content are widely misused by various parties, the occurrence of violations of their main rights moral rights is less realized by various parties. It is the duty of all parties to create the protection of moral rights because rights are elements that must be protected in a digital copyright work. This research aims to find out the regulation of aspects of moral rights in Law No. 28 of 2014 on Copyright. This research uses normative juridical research methods using the legal sources of literature. The protection of moral rights is an important issue in the protection of intellectual property. National regulations are expected to protect the moral rights of copyright creators/owners, especially digital copyright works.